Economic incentives reduce plastic inputs to the ocean. (October 2018) - Schuyler, Qamar; Hardesty, Britta Denise; Lawson, TJ; Opie, Kimberley; Wilcox, Chris
Abstract: Mismanaged waste and marine debris have significant detrimental effects on wildlife, public health, and the economy. Container deposit legislation (CDL) is one of the many legislative actions proposed by lawmakers to curb the amount of debris entering the ocean. Beverage containers are consistently among the most commonly littered items, so effective legislation could prove a significant lever to reduce debris inputs to the marine environment. The effectiveness of CDL at reducing the amount of beverage container litter on the coasts of two countries, Australia and the United States, was evaluated by comparing results of debris surveys in states with and without cash incentives for returned beverage containers. The proportion of containers found in coastal debris surveys in states with CDL was approximately 40% lower than in states without CDL. Additionally, CDL states had a higher ratio of lids to bottles, further demonstrating the effectiveness of the incentives in removing bottles from the waste stream. The reduction in beverage containers in the presence of CDL was greater in areas with low socio-economic status, where debris loads are highest. These results provide strong evidence that fewer beverage containers end up as mismanaged coastal waste in states that provide a cash refund for returned beverage containers. Findings are discussed in the context of global governance, social license and opportunities to reduce land-based litter inputs to the ocean. Highlights: Marine debris has significant detrimental effects on wildlife, public health, and the economy. CDL reduces beverage containers in the coastal environment. The proportion of beverage containers littered on the coasts is 40% lower in states with Container Deposit Legislation (CDL). States with CDL had more littered lids than other states, because legislation only targets containers. CDL reduces beverage containers more in poorer areas, where debris loads are highest.